O Nexo entre Concepções e Práticas de Ensino da Geografia em Moçambique: Estudo de caso - Língua, Januário (2006)
This dissertation is to be considered within the broader scope of a reflection on the teaching-learning process in the secondary school curriculum. It focuses on the relation between conceptions in Geography and the way they are taught. The field research related to this dissertation was conducted in ESG II (the second cycle of General Secondary Education grades 11 and 12) in three public schools in Maputo Province and Maputo City. Due to some characteristics that became evident in the course of work, within ESG II major attention was given to grade 12, whose central theme is Human Geography. The renewal of Geography and its teaching has been taking place as a result of two conceptions and/or their variants that developed in the process of their evolution: the positivist and the historicist conceptions. These conceptions, developing in different ways, corresponding to the different countries and their socio-historic dynamics, have their repercussions in teaching practice, sometimes without a clear connection with the und erlying conception. The methodological approach is based upon the postulates of qualitative research, which considers knowledge and its construction as a living and dynamic relation between subject and object. The dissertation is developed in four chapters: the first is a theoretical-methodological introduction; the second is dedicated to the analysis of the field research; the third is a historic description of the evolution of Geography and its teaching in Mozambique, in particular in ESG II; the fourth presents the conclusions and suggestions. The results of the research indicate that there is no correspondence between the evolution and renovation of Geography at the conceptual level and its teaching, the latter showing evidence of distortions, because of its markedly traditional character.